2020
DOI: 10.1002/iid3.387
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID‐19 contribute to development of neurological disease?

Abstract: Background Although coronavirus disease 2019 (COVID‐19) has been associated primarily with pneumonia, recent data show that the causative agent of COVID‐19, the coronavirus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), can infect a large number of vital organs beyond the lungs, such as the heart, kidneys, and the brain. Thus, there is evidence showing possible retrograde transmission of the virus from the olfactory epithelium to regions of the brain stem. Methods This is a literature review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 92 publications
(95 reference statements)
0
59
0
6
Order By: Relevance
“…Besides respiratory and gastrointestinal tracts, there is accumulating evidence that SARS-CoV-2 has a tropism for the nervous system, leading to neurological sequelae including immune-mediated demyelinating disease, cerebrovascular damage, and neurodegeneration [54][55][56]. SARS-CoV-2 may infect neurons, microglia, astrocytes, pericytes/endothelial cells, ependymocytes/choroid epithelial cells, and neural stem/progenitor cells [57,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides respiratory and gastrointestinal tracts, there is accumulating evidence that SARS-CoV-2 has a tropism for the nervous system, leading to neurological sequelae including immune-mediated demyelinating disease, cerebrovascular damage, and neurodegeneration [54][55][56]. SARS-CoV-2 may infect neurons, microglia, astrocytes, pericytes/endothelial cells, ependymocytes/choroid epithelial cells, and neural stem/progenitor cells [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanisms by which SARS-CoV-2 impairs the CNS are not completely known, neuroinflammation and blood-brain barrier (BBB) disruption have been suggested to contribute to neurological symptoms and poor prognosis [60][61][62]. Indeed, profound neuroinflammatory changes have been reported in COVID-19 patients [63], which could be due to direct infection of the CNS, microglia activation, and activated peripheral immune response to SARS-CoV-2 infection [56,64], all of which could be worsened by obesity [65,66]. Significant peripheral inflammation during COVID-19 could disrupt the BBB and contribute to COVID-19 neuropathologies [67].…”
Section: Discussionmentioning
confidence: 99%
“…In the model, disease-1 can emulate the role of, for instance, measles or even COVID-19. In fact, COVID-19, in addition to causing respiratory problems, cerebrovascular disorders, neurological injuries, and psychological distress ( Mahalakshmi et al., 2021 ), can also suppress host immunity ( Remy et al., 2020 ), which can increase the vulnerability to future infections as measles does. In the model, disease-2 can be any non-vaccine preventable infection, such as hepatitis C, or a vaccine-preventable infection, but with poor adherence to vaccination, such as hepatitis A ( Johnson et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that viral infections can trigger brain endothelial and epithelial cells to produce cytokines that impair neuronal firing in the hippocampus, leading to depressive-like symptoms [51]. Summarizing the clinical symptoms reported in SARS virus infection, there is thus the possibility that SARS virus infection affected mood by altering the 5-HT system [52]. Therefore, 5-HTR-targeting drugs could be considered as a potential approach in therapies being developed for treating anxiety and depression induced by the COVID-19 infection.…”
Section: Role Of 5-ht In the Viral Infectionmentioning
confidence: 99%